Sistem Pakar Untuk Mendiagnosa Penyakit Kucing Menggunakan Metode Forward Chaining Dan Certainty Factor - Ferdy Maulana; Heri Haerudin (CV. Multi Kreasi Media, 2024)
Cats are very popular pets all over the world. There are many varieties of cats that can be used in a variety of ways. However, with the growing interest in domestic cats, some cat owners have inadequate knowledge of how to treat and identify symptoms of disease in their cats. Therefore, it is necessary for an expert system that can provide initial information and help in identifying and treating cat disease. The study aims to create a system of forward-based experts chaining the diagnosis of cat disease based on symptoms. It employs a new method, factor, that provides assurance about the patient's condition in relation to diagnosis, and compared with other conditions to attaining the goal. Thus, more accurate data can be given regularly. The established systems of experts produce a display diagnosing the cat's disease-looking cat, which gives the public access to symptoms of the disease suffered by its pet cat. With this system of things, the owner of a cat can take immediate medical action or take it to a veterinarian. This system of experts, therefore, can be a guide to storing knowledge and helping communities in caring for their pet cats